A Novel Sweetpotato Transcription Factor Gene IbMYB116 Enhances Drought Tolerance in Transgenic Arabidopsis - Zhou, Yuanyuan; Zhu, Hong; He, Shaozhen; Zhai, Hong; Zhao, Ning; Xing, Shihan; Wei, Zihao; Liu, Qingchang (Frontiers in Plant Science, 2019)
Several members of the MYB transcription factor family have been found to regulate growth, developmental processes, metabolism and biotic and abiotic stress responses in plants. However, the role of MYB116 in plants is still unclear. In this study, a MYB transcription factor gene IbMYB116 was cloned and characterized from the sweetpotato [Ipomoea batatas (L.) Lam.] line Xushu55-2, a line that is considered to be drought resistant. We show here that IbMYB116 is a nuclear protein and that it possess a transactivation domain at the C terminus. This gene exhibited a high expression level in the leaf tissues of Xushu55-2 and was strongly induced by PEG6000 and methyl-jasmonate (MeJA). The IbMYB116-overexpressing Arabidopsis plants showed significantly enhanced drought tolerance, increased MeJA content and a decreased H2O2 level under drought stress. The overexpression of IbMYB116 in Arabidopsis systematically upregulated jasmonic acid (JA) biosynthesis genes and activated the JA signaling pathway as well as reactive oxygen species (ROS)-scavenging system genes under drought stress conditions. The overall results suggest that the IbMYB116 gene might enhance drought tolerance by activating a ROS-scavenging system through the JA signaling pathway in transgenic Arabidopsis. These findings reveal, for the first time, the crucial role of IbMYB116 in the drought tolerance of plants.